2006
DOI: 10.1007/s00464-006-0088-2
|View full text |Cite
|
Sign up to set email alerts
|

An antireflux stent versus conventional stents for palliation of distal esophageal or cardia cancer: a randomized clinical study

Abstract: Antireflux stents may be used without increased risk of complications, mortality, esophageal symptoms, or reduced global quality of life. These results should encourage large-scale randomized trials that can establish potentially beneficial effects of antireflux stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 12 publications
1
28
1
3
Order By: Relevance
“…In our prospective case series, a rather prolonged survival (median survival, 202 days) was observed in contrast to other studies [4,22]. In these patients, the use of covered SEMS permitted a significant reduction in the incidence of ingrowth (3%) and the need for additional endoscopic intervention to restore patency [4].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In our prospective case series, a rather prolonged survival (median survival, 202 days) was observed in contrast to other studies [4,22]. In these patients, the use of covered SEMS permitted a significant reduction in the incidence of ingrowth (3%) and the need for additional endoscopic intervention to restore patency [4].…”
Section: Discussioncontrasting
confidence: 51%
“…Indeed, gastroesophageal reflux was observed primarily in patients with tumor of the lower esophagus/GEJ (18 of 21 patients with gastroesophageal reflux). Symptoms of gastroesophageal reflux are reported to occur in 5-15% of patients with standard open stents [19,23], whereas they affect up to one-third of patients who have received a stent for a malignant stricture of the GEJ, especially when they are in the supine position [22,35]. It is our policy to prescribe proton pump inhibitors for patients with SEMS placement for esophagogastric tumors, and we advise patients to sleep in an upright position and to avoid having late-night meals.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies had a score of 4 points [6,7], eight studies had scores of 3 [4,8,10,12,[14][15][16]18], five studies scored 2 [3,9,11,13,17], and one study received one point [5]. The baseline characteristics of the patients in the trials included are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…All randomized control trials (RCTs) concerning esophageal and gastroesophageal junction palliation were identified [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Studies using the conventional prosthetic tubes (Celestin or Mackler tube) were excluded since the method has fallen out of favor.…”
Section: Literature Searchmentioning
confidence: 99%
“…Mean or median patient survival has been reported to vary from 10 to 20 weeks in patients who underwent SEMS placement to alleviate malignant esophageal and GEJ obstructions with variable underlying malignancy [34][35][36]. However, few reports have addressed stent patency duration and factors associated with stent patency.…”
Section: Discussionmentioning
confidence: 97%